Regulatory theory : foundations and applications - Drahos, Peter, 1955- (ANU Press, 2017)
This volume introduces readers to regulatory theory. Aimed at practitioners, postgraduate students and those interested in regulation as a cross-cutting theme in the social sciences, Regulatory Theory includes chapters on the social-psychological foundations of regulation as well as theories of regulation such as responsive regulation, smart regulation and nodal governance. It explores the key themes of compliance, legal pluralism, meta-regulation, the rule of law, risk, accountability, globalisation and regulatory capitalism. The environment, crime, health, human rights, investment, migration and tax are among the fields of regulation considered in this ground-breaking book. Each chapter introduces the reader to key concepts and ideas and contains suggestions for further reading. The contributors, who either are or have been connected to the Regulatory Institutions Network (RegNet) at The Australian National University, include John Braithwaite, Valerie Braithwaite, Peter Grabosky, Neil Gunningham, Fiona Haines, Terry Halliday, David Levi-Faur, Christine Parker, Colin Scott and Clifford Shearing.